Early dolomitization and recrystallization of the Lower-Middle Ordovician carbonates in western Tarim Basin (NW China). (January 2020) - Guo, Chuan; Chen, Daizhao; Qing, Hairuo; Zhou, Xiqiang; Ding, Yi
Abstract: The Lower-Middle Ordovician shallow-marine carbonates in western Tarim Basin were dolomitized to different degrees. The resultant dolomites are mainly concentrated in the successions of platform interior to shallow subtidal shoal, and display an upward decrease in abundance. Based on petrographic textures, three types of matrix dolomites were identified: (1) very finely to finely crystalline, nonplanar-a to planar-s dolomite (Md1), (2) finely to medium crystalline, planar-e(s) dolomite (Md2), and (3) finely to coarsely crystalline, nonplanar-a dolomite (Md3). Origins of matrix dolomites are interpreted on the basis of field investigation, petrography and isotopic (O, C and Sr) geochemistry. Md1 dolomite was formed from slightly evaporated (i.e., mesosaline to penesaline) seawater in near-surface to very shallow burial settings, possibly facilitated by microbial mediation (i.e., bacterial sulphate reduction; BSR). Md2 dolomite was precipitated from connate seawater stored in coeval limestone in shallow burial realms. In contrast, Md3 dolomite was likely formed as a consequence of intense recrystallization of early-formed dolomites (e.g., Md1) at depths. The formation of early matrix dolomites (i.e., Md1) was likely determined by depositional facies and sea-level variations of variable orders. This study provides a useful analogue to understand the dolomitization processes related to depositional facies and variable-order sea-level fluctuations in the Tarim Basin and elsewhere. Highlights: Dolomitizing fluids were derived from slightly evaporated seawater and connate coeval brines. Early dolomite was formed by the reflux of mesosaline to penesaline seawater. Late dolomite likely resulted from intense recrystallization of early-formed dolomites. Early dolomite development was likely determined by depositional facies and sea-level variations of variable orders.